2020
DOI: 10.1016/j.celrep.2020.107954
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubule mTORC1 Is a Central Player in the Pathophysiology of Diabetic Nephropathy and Its Correction by SGLT2 Inhibitors

Abstract: Summary Diabetic kidney disease (DKD) increases the risk for mortality and is the leading cause of end-stage renal disease. Treatment with sodium-glucose cotransporter 2 inhibitors (SGLT2i) attenuates the progression of DKD, especially in patients with advanced kidney disease. Herein, we show that in diabetes, mTORC1 activity is increased in renal proximal tubule cells (RPTCs) along with enhanced tubule-interstitial fibrosis; this is prevented by SGLT2i. Constitutive activation of mTORC1 in RPTCs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 44 publications
(59 reference statements)
2
85
2
Order By: Relevance
“…In disagreement with previous reports, we found that KPTC proliferation was reduced rather than increased, and there was no evidence for epithelial-mesenchymal transition, suggesting that tubular cell dedifferentiation does not play a major role in kidney dysfunction in this model [38]. [38]. Importantly, moderate reduction of mTORC1 activity by conditional, heterozygous deletion of Raptor in KPTCs completely prevented fibrosis and preserved kidney function [38].…”
Section: Accepted Articlecontrasting
confidence: 99%
See 3 more Smart Citations
“…In disagreement with previous reports, we found that KPTC proliferation was reduced rather than increased, and there was no evidence for epithelial-mesenchymal transition, suggesting that tubular cell dedifferentiation does not play a major role in kidney dysfunction in this model [38]. [38]. Importantly, moderate reduction of mTORC1 activity by conditional, heterozygous deletion of Raptor in KPTCs completely prevented fibrosis and preserved kidney function [38].…”
Section: Accepted Articlecontrasting
confidence: 99%
“…Consistent with this paradigm, treatment of KPTCs with SGLT2i decreased glycolytic flux [38] . In disagreement with previous reports, we found that KPTC proliferation was reduced rather than increased, and there was no evidence for epithelial-mesenchymal transition, suggesting that tubular cell dedifferentiation does not play a major role in kidney dysfunction in this model [38]. [38].…”
Section: Accepted Articlementioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, the activation of the mTOR pathway is involved in the increased expression of profibrotic cytokines, such as TGF-β1 and connective tissue growth factor, and subsequent interstitial fibrosis of DKD [ 34 , 35 ]. Furthermore, proximal tubular cell-specific Raptor heterozygous-deficient mice exhibit reduced tubular fibrosis and reduced renal function under diabetic conditions [ 36 ]. These results suggest that the abnormal activation of mTORC1 is involved in the pathogenesis of tubular damage in DKD.…”
Section: Tubular Cell Injury In Typical Dkd and Mtorc1mentioning
confidence: 99%